Networked in or networked out? Learners' experiences of completing a PhD on a part-time basis - O'Regan, Maeve (Trinity College Dublin. School of Education. Discipline of Education, 2022)
Doctoral education policy and practice in Europe tends to recognise candidature in terms of the full-time PhD researcher. Part-time doctoral candidates have been described as invisible in policy (Neumann and Rodwell, 2009) and campus life (Gardner and Gopaul, 2012) due to often managing studies in tandem with work and roles (Watts, 2008). This presented challenges in terms of developing a methodology for this study as doctoral education has primarily focused on the experiences of the full-time researcher and has emphasised the role of socialisation (Weidman and Stein, 2003) of the learner into the academic department and institution as influencing academic progression and quality of the doctoral experience. Researchers recommend further studies on the experiences of non-traditional doctoral candidates, for example part-time researchers (Zahl, 2015) beyond an assumption of the learner as full-time (Hopwood, Harris-Heummert McAlpine and Wagstaff, 2011) and situated in the academic institution (Pearson, Evans and Macauley, 2016). A questionnaire and a semi-structured interview protocol were developed within this research to explore various aspects of the part-time learner's experience of navigating the PhD. This included access to doctoral programme resources and support (face-to-face and online) and the role of personal agency and help-seeking behaviour as influencing doctoral progression and completion. Eighteen full and part-time doctoral candidates from a single university in Ireland participated in a preliminary phase of the study to develop the research instruments. Additional interviews were conducted with eight other individuals including academic staff, postgraduate student advisors and four individuals who had undertaken an alternative form of doctoral education (part-time) to the traditional PhD. Responses suggested that completed/completing PhD candidates had a greater sense of what had influenced progression with doctoral studies than early or mid-stage candidates. Eighteen individuals who completed a part-time PhD in (5) different universities in Ireland participated in the main study. The findings highlighted the uniqueness of each learner's experience of navigating doctoral studies and illustrated the importance of developing online and face-to-face supports for learners at a distance from the academic institution/campus setting. This study addressed a gap in existing research namely by adding the completed part-time learners' voice to discourse within doctoral education. Recommendations from this study included the adoption of a person-centred and comprehensive approach to supporting doctoral candidates, particularly learners with limited access to the campus environment due to balancing studies with other roles.
APPROVED
Keywords: Part-time; PhD; completed; agency; networks; support